Evaluasi Praktik Otonomi Daerah sebagai Upaya Optimalisasi Pembangunan Daerah - Afrinda, naswa; Nazarilmi, Aina Mahda; Aswanda, Athalia; Musyafa, M. Naufal (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
The development of regional autonomy is a strategic step in equitable and sustainable regional development. In this framework, evaluation of the implementation of regional autonomy practices becomes a necessity. Regional autonomy provides opportunities for local governments to manage resources and plan development according to local needs, as well as increasing community participation in the decision- making process. However, the number of underdeveloped areas in Indonesia is often debated, with factors such as corruption and funds not being channeled properly. Evaluation of regional autonomy practices is important to identify successes, obstacles and challenges in efforts to optimize regional development, thereby enabling policy improvements and adjustments to increase the effectiveness and efficiency of implementing regional autonomy. The research method used is a normative juridical research method. This research will collect data through literature study and will analyze the data qualitatively. The evaluation results show varying results in various regions. To optimize regional development, continuous improvement efforts are needed, such as increasing apparatus capacity, stricter supervision, incentives for high-achieving regions, and encouraging transparency and accountability in budget management.